Identity in Personal Recovery for Mothers With a Mental Illness - Hine, Rochelle Helena; Maybery, Darryl John; Goodyear, Melinda Jane (Frontiers in Psychiatry, 2019)
Developing a “positive identity” is considered a core component of personal recovery, and mothering offers meaning in life and a valued identity. Few studies have highlighted the factors influencing identity within a personal recovery paradigm for mothers with mental illness. This study explores how mothers describe their identity in relation to recovery, including the factors that influence identity. Using constructivist grounded theory methodology, in-depth interviews were conducted with 17 women who were mothers and experienced mental illness. Women defined their self-concept broadly, accentuating motherhood, but also including vocational, community and social roles. Analysis revealed six categories: defining self, becoming a mother, being a “good” mum, feeling different, doing it my way and speaking out. Valuing identity in parenting was found to be linked to recovery. Services may facilitate personal recovery by supporting mothers to enhance a self-concept associated with mothering, as well as other diverse attributes and roles.